Lipoblastomas and liposarcomas in paediatric patients: A case series. Issue 3 (March 2021) - McRae, Joyce J.L.H; Hashmi, Asra; Radulescu, Andrei; Carter, Cody S.; Khan, Faraz A.
Lipoblastomas and liposarcomas are rare causes of soft tissue masses in paediatric patients. In this retrospective clinical case series we identified 11 patients from our paediatric database (10 with a lipoblastoma and one with a liposarcoma) who had attended our hospital between 1998 and 2019. The median age of patients with lipoblastoma was 29 months. All lipoblastoma cases were managed with surgical excision and histological examination. The 18-year old patient with liposarcoma presented with a metastatic and unresectable tumour that was unresponsive to chemotherapy and radiation. Our experience demonstrates the importance of differentiating the type of soft tissue mass in children.